Acute kidney injury in hematological patients treated with CAR-T cells: risk factors, clinical presentation and impact on outcomes - Elisa Russo; Massimiliano Gambella; Anna Maria Raiola; Elena Beltrametti; Valentina Zanetti; Giuseppe Chirco; Francesca Viazzi; Emanuele Angelucci; Pasquale Esposito (Scientific Reports)
Abstract Chimeric antigen receptor T-cell (CAR-T) therapy has revolutionized the treatment of hematologic malignancies, yet it carries significant risks, including acute kidney injury (AKI). In this study, we investigated the risk factors and clinical impact of AKI in patients undergoing CAR-T cell therapy. This retrospective study involved hematologic patients treated with CAR-T therapy. Clinical and laboratory data were collected, and clinical outcomes were monitored during follow-up after CAR-T infusion. AKI was defined according to KDIGO criteria. The outcome measures included early mortality, overall survival (OS), and disease-free survival (DFS). Among the 48 patients analyzed, 14 (29%) developed AKI, with a mean onset of 6 days after CAR-T infusion. The risk of AKI was associated with baseline performance status (OR 8.65, IC95% 6.2–12, p = 0.032) and the development of severe cytokine release syndrome post-therapy (OR 16.4 95%CI 1.9-138.5, p = 0.01). Patients with AKI more frequently required intensive care. Furthermore, severe AKI was independently associated with worse clinical outcomes, including reduced OS and DFS (HR 18.2, 95%CI 2.6–27.3, p = 0.003). Additionally, patients who developed AKI post-CAR-T therapy were more likely to progress to chronic kidney disease during follow-up. In conclusion, frail patients undergoing CAR-T therapy are at an increased risk of developing AKI, which can significantly affect both short- and long-term outcomes. Preventive strategies and early recognition of AKI are essential in these patients.